Laboratory health and safety dictionary - Gottschall, W. Carl (Wiley, 2001)
This authoritative compendium of chemical health and safety terms and concepts contains approximately 2,500 entries covering the broad spectrum of health and safety issues, including all essential elements of a chemical hygiene plan, safety procedures, chemical exposures, etc.